Future of Work: Adapting HR Management Strategies to Changes in Digital Work Structures - Arimessa, Willy; Puterisari, Dwi Utami (Maneggio, 2026)
The development of digital technology, automation, and artificial intelligence has driven fundamental changes in the structure of work known as the Future of Work phenomenon. These changes not only affect the type and character of work but also alter patterns of work relationships, competency requirements, and expectations regarding the role of human resources in organizations. This condition demands the adaptation of HR management strategies that can respond to the dynamics of digital work systematically and sustainably. This study aims to analyze how organizations adapt HR management strategies to address changes in the structure of digital work and its implications for organizational performance, engagement, and sustainability. The study used a qualitative approach with a case study design to gain an in-depth and contextual understanding of HR adaptation practices. Data were collected through in-depth interviews, observations, and documentation studies, then analyzed thematically. The results show that changes in the structure of work encourage a shift in the role of HR management from an administrative function to a strategic function oriented towards talent management, continuous learning, and flexible work systems. Adapting HR strategies has been shown to contribute to improved organizational performance, strengthened employee engagement, and supported long-term sustainability. These findings emphasize the importance of integrating business strategy, technology, and HR management in facing the challenges of the Future of Work.